PEDAGOGY IN HOSPITAL SETTING - Oliveira, Pedro Anastácio de; Santos, Gustavo Henrique dos; Coutinho, Diogenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
Hospital Pedagogy comes against a professional reality in which we act and experience daily. Faced with this reality where children are hospitalized, as a Pedagogy student, we perceive the possibilities for the pedagogue to act in a space where children and adolescents are often forgotten as children, adolescents and students, ignoring everything they left outside from the hospital seeing only the clinical part of your treatment. Despite having a set of laws, national and international declarations that highlight education and health as a priority focus for the promotion of life, these rights are far from being achieved and/or becoming a reality for the popular classes. To exemplify, we can mention Resolution No. 41 of October 13, 1995, of the National Council for the Rights of Children and Adolescents, which provides for the rights of hospitalized children and adolescents. Its text provides that every hospitalized child has the right to enjoy some form of recreation, health education programs and monitoring of the school curriculum during their hospital stay, since these children, if they were not hospitalized, would be experiencing pedagogical experiences and having their cognitive and development process stimulated by the school environment.